ANALISIS PENGARUH KUALITAS LAYANAN DAN NILAI NASABAH TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING - Suhastomo, Reza; Khasanah, Imroatul (Diponegoro Journal of Management, 2015)
This paper is based on the existence of customer dissatisfaction of PD. BPR Bank Pasar Kabupaten Kudus which can be seen through the data increase of deposits customers who closed accounts during the period June - September 2014. By looking at existing problems, this study aimed to analyze the influence of service quality and customer value service to the customer satisfaction to creat deposits customer loyalty PD. BPR Bank Pasar Kabupaten Kudus. This study sample of 100 customers. Question is given by using questionnaire consisting of closed and open question. Respondent,s answers were analyzed with two stage regression using SPSS. Based on analyzed conducted, it was concluded that the variable service quality and customer value has positive and significant impact to customer satisfaction. Then, customer satisfaction has positive and satisfaction impact to Customer Loyalty in PD. BPR Bank Pasar Kabupaten Kudus. The result of this study is expected to be used as information for PD. BPR Bank Pasar Kabupaten Kudus and further research.